Diminished reality considering background structures - Kawai, Norihiko; Sato, Tomokazu; Yokoya, Naokazu (2013 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2013)
This paper proposes a new diminished reality method for 3D scenes considering background structures. Most conventional methods using image inpainting assumes that the background around a target object is almost planar. In this study, approximating the background structure by the combination of local planes, perspective distortion of texture is corrected and searching area is limited for improving the quality of image inpainting. The temporal coherence of texture is preserved using the estimated structures and camera pose estimated by Visual-SLAM.